Genital and systemic immune effects of the injectable, contraceptive norethisterone enanthate (NET‐EN), in South African women. (10th March 2021) - Molatlhegi, Refilwe P.; Ngcobo, Samkelisiwe; Liebenberg, Lenine J. P.; Ngcapu, Sinaye; Mabhula, Amanda; Leslie, Alasdair; Mchunu, Nobuhle; Zondi, Mthobisi M.; Adamson, John H.; Govender, Katya; Samsunder, Natasha; Karim, Salim S. Abdool; et al.
Abstract: Problem: Injectable hormonal contraceptives (IHC) have been associated with altered mucosal and systemic milieu which might increase HIV risk, but most studies have focused on DMPA and not NET‐EN, despite the growing popularity and lower HIV risk associated with the latter in observational studies. Method of study: We used high‐performance liquid chromatography in combination with tandem triple quadrupole mass spectrometry (HPLC‐LC‐MS/MS) to measure steroid hormones in plasma samples of CAPRISA004 study participants. Concentrations of 48 cytokines were measured in the cervicovaginal lavage (CVL) and plasma, and their expression was compared between participants with detectable NET‐EN (n = 201) versus non‐detectable IHC (n = 90). Each log10 cytokine concentration was tested as an outcome in linear‐mixed models, with NET‐EN detection as the main explanatory variable. Multivariable models were adjusted for potential confounders. Results: In bivariate analysis, detectable NET‐EN was associated with reduced cervicovaginal M‐CSF ( P  = 0.008), GM‐CSF ( P  = 0.025) and G‐CSF ( P  = 0.039), and elevated levels MIF ( P  = 0.008), IL‐18 ( P  = 0.011), RANTES ( P  = 0.005) and IL‐1Rα ( P  < 0.001). Lower G‐CSF ( P  = 0.011) and elevated IL‐1Rα ( P  = 0.008) remained significant in adjusted models. Multivariable analyses of plasma samples obtained from NET‐EN‐detectable women showed a significant increase in IP‐10 ( P  = 0.026) and reductions in TNF‐β ( P  = 0.037), RANTES ( P  = 0.009), and M‐CSF ( P  < 0.001). While similar growth factor reduction in CVL was noted for both DMPA and NET‐EN, similar trends were not observed for endogenous progesterone. Conclusions: Detectable NET‐EN was associated with reduced growth factors in the plasma and genital tract; particularly G‐CSF and M‐CSF. Our results suggest that while NET‐EN is not inflammatory, it may have important immunological effects.